2015
DOI: 10.1039/c5ra12214g
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Rapana thomasiana hemocyanin with choline amino acid salts significantly enhances its antiproliferative activity against MCF-7 human breast cancer cells

Abstract: This is the first study on the interactions of ionic liquids with large metalloproteins, in particular hemocyanins (Hcs). At first, complexes of a Hc from Rapana thomasiana (RtH) with a series of biocompatible choline amino acid salts [Chol][AA] were obtained. Applying UV-vis spectroscopy, Fouriertransformed infrared spectroscopy and differential scanning calorimetry the effect of these organic salts on the structure and thermal stability of RtH was assessed. Then, the cytotoxic effect of RtH- [Chol][AA] on br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Amino acid-based ILs are another promising class of biocompatible ILs that have received some interest in recent years (Chevrot et al 2015;Guncheva et al 2015;Sankaranarayanan et al 2012;Tarannum et al 2018). Amino acids have been mostly incorporated as anions, especially with imidazolium or choline cations to produce a biocompatible or Bgreen^IL.…”
Section: Choline-based Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid-based ILs are another promising class of biocompatible ILs that have received some interest in recent years (Chevrot et al 2015;Guncheva et al 2015;Sankaranarayanan et al 2012;Tarannum et al 2018). Amino acids have been mostly incorporated as anions, especially with imidazolium or choline cations to produce a biocompatible or Bgreen^IL.…”
Section: Choline-based Ilsmentioning
confidence: 99%
“…Amino acids have been mostly incorporated as anions, especially with imidazolium or choline cations to produce a biocompatible or Bgreen^IL. Guncheva et al (2015) tested a series of choline-amino acid ILs on a hemocyanin and found that the thermal stability was lower in all ILs tested than in the control. Tarannum et al (2018) recently studied the effect of four choline-based amino acid ILs (choline serinate, threoninate, lysinate, and phenylalaninate) on the structural stability of collagen and had similar findings; they determined that competing hydrogen bonds between the ILs and OH groups on the collagen may be responsible for the destabilization observed.…”
Section: Choline-based Ilsmentioning
confidence: 99%
“…Indeed, though the use of ChoAA-ILs in the field of biomass processing for which they were originally developed-they possess the amazing property of solubilizing lignin selectively from rice straw-has steadily continued to grow (Hou et al 2013b;Reddy 2015;Wang et al 2016;To et al 2018), the powerful solubilization properties of these liquids were extended to other systems, like drugs (Alawi et al 2015), to the extraction of noxious substances in cigarette smoke (Zhang et al 2016), and to lignite and thermal coal pre-treatment (To et al 2017). In addition, these compounds have found use as lubricants (Mu et al 2015;Jiang et al 2018;Zhang et al 2018;Wu et al 2018), as CO 2 capture agents (Zhang et al 2013;Bhattacharyya and Shah 2016;Saptal and Bhanage 2017), and as antimicrobials (Foulet et al 2016), in topical formulations for drug delivery (De Almeida et al 2017), and they have shown to possess selective antiproliferative activity against some breast cancer cell lines when complexed with hemocyanins (Guncheva et al 2015). Probably, the most striking feature of ChoAA-ILs lies in the fact that this variety of properties goes along with their substantial harmlessness.…”
Section: Introductionmentioning
confidence: 99%
“…HeLa cell is the most widely used model cell line for studying human cellular and molecular biology [ 39 , 40 ]. Evidence suggests that Rapana thomasiana HMC showed antiproliferative activity against human breast cancer MCF-7 and cervical cancer HeLa cells [ 41 ]. However, the antiproliferative effect of arthropod HMCs have not been reported.…”
Section: Discussionmentioning
confidence: 99%